Unexpected hepatitis B virus infection after liver transplantation — United States, 2014–2019. Issue 9 (7th September 2021) - Bixler, Danae; Annambhotla, Pallavi; Montgomery, Martha P.; Mixon‐Hayden, Tonya; Kupronis, Ben; Michaels, Marian G.; La Hoz, Ricardo M.; Basavaraju, Sridhar V.; Kamili, Saleem; Moorman, Anne
Abstract : This article describes 14 cases of donor‐derived hepatitis B virus infection in liver transplant recipients despite the donors having had negative testing for hepatitis B prior to organ procurement. The majority of the involved donors were also seropositive for hepatitis C and had a history of injection drug use. This report underscores the need for serial posttransplant hepatitis B testing of recipients, even when initial donor and recipient testing is negative, and the importance of pretransplant hepatitis B vaccination in transplant candidates.